2011
DOI: 10.1007/s11136-011-9909-4
|View full text |Cite
|
Sign up to set email alerts
|

What do people include when they self-rate their health? Differential associations according to health status in community-dwelling older adults

Abstract: This implies that SRH has differential associations depending on health status, which should be taken into account in interpreting any research with SRH as predictor or criterion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 42 publications
4
40
0
3
Order By: Relevance
“…Subramanian et al (2003) found a very large effect of households on poor self-rated health in Chile (VPC of 47%), however they made use solely of the binary indicator (SRH). Van Minh et al (2010) reported a share of only 15% of perceived good health variability among Vietnamese people over 50 which, however, is a different outcome and cannot simply be seen as the other side of the coin of our outcome (Benyamini et al 2003;Kaplan and Baron-Epel 2003;Schüz et al 2011). The only study concerning a developed country is based in the USA (Ferrer et al 2005) and revealed a maximum variability share attributable to the family context of 9.9% for PCS and 15.4% for MCS, controlled for individual covariates The authors used census families, which include all persons related to the household's head by blood or marriage, disregarding the co-residence requisite.…”
Section: Discussionmentioning
confidence: 89%
“…Subramanian et al (2003) found a very large effect of households on poor self-rated health in Chile (VPC of 47%), however they made use solely of the binary indicator (SRH). Van Minh et al (2010) reported a share of only 15% of perceived good health variability among Vietnamese people over 50 which, however, is a different outcome and cannot simply be seen as the other side of the coin of our outcome (Benyamini et al 2003;Kaplan and Baron-Epel 2003;Schüz et al 2011). The only study concerning a developed country is based in the USA (Ferrer et al 2005) and revealed a maximum variability share attributable to the family context of 9.9% for PCS and 15.4% for MCS, controlled for individual covariates The authors used census families, which include all persons related to the household's head by blood or marriage, disregarding the co-residence requisite.…”
Section: Discussionmentioning
confidence: 89%
“…First, this study is limited to self-perceived health and we are not able to disentangle the various dimensions of self-perceived health in the current study with the data at hand. Self-rated health is, however, the most widely regarded valid and reliable indicator of health status, although we acknowledge the meaning of self-rated health to differ between individuals (Schüz et al 2011). Self-reported health is a multidimensional and multifaceted construct (Liang 1986), including-among others-functional status, behavioural factors, and interpersonal resources.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that psychological factors in particular can be crucial for self-perceived health. Experiencing depression is a key predictor of self-rated health besides physical symptoms (Schneider et al 2004;Schüz et al 2011). As our target population are people in young and middle adulthood, physical impairments might be less important and mental problems might determine to a larger extent the self-perception of health.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although individuals' self-rated health status will change over time, the change in self-rated health will vary depending on population and period of following time. For example, a substantial proportion of participants (from 15% to 40%) changed their reported health status between the different interviews and response reliability was related to socio-demographic factors, such as age, income and education [19]- [21]. As for elder population, although participants can change in both directions, more participants will change their self-rated health from higher level to lower level.…”
Section: Discussionmentioning
confidence: 99%